Influence of thermochemical gas nitriding on morphology and dry wear of Duplex-S32205 - Paijan, Lailatul Harina; Maleque, Md. Abd.; Abdollah, Mohd Fadzli; Rosli, Nor Ana (Malaysian Tribology Society (Mytribos), 2025)
Surface modification is needed to improve the surface quality of Duplex-S32205 due to limitation of low hardness and wear properties of this material. The aim of this work is to evaluate the incorporation of nitrogen gas diffusion via low thermochemical gas nitriding process at temperature of 500 °C for duplex stainless steel S32205. The nitriding holding duration was varying for 4, 8 and 12 hours in the nitrogen environment of ammonia (NH4) and nitrogen (N2) gaseous. Microhardness and wear properties of the gas nitride layer were examined using microhardness tester, scanning electron microscopy and ball-on-disc tribotester. The nitride layer with holding duration of 12 hours produced the highest thickness layer and hardness of 88 µm and 603.4 HV, respectively. Meanwhile, the wear rate improved to 42 % and CoF to 30% compared to untreated material. It was demonstrated that nitriding process is capable to produce hard surface layer on S32205 with improved wear resistance properties.